LITERATURE REVIEW ON ISLAMIC EDUCATION LEARNING DESIGN STRATEGIES TO COUNTER RADICALIZATION AMONG TEENAGERS - Neneng Hilda (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
AbstractThis article explores Islamic education learning design strategies aimed at countering radicalization among teenagers, with a particular focus on the role of Islamic education in promoting tolerance, moderation, and critical thinking. The literature review examines key educational theories and frameworks, including student-centered learning (SCL), the integration of wasathiyyah (moderation), and the importance of interreligious literacy. The article discusses the challenges faced by Islamic education, such as technological barriers, curriculum integration, and resource limitations, alongside the opportunities presented by modern educational practices and technology, including mobile learning (m-learning) and digital innovations. Additionally, case studies from various countries highlight the effectiveness of Islamic education strategies in countering radicalization, particularly through promoting moderate Islamic values and community engagement. The review also emphasizes the need for teacher training and the integration of social justice themes in Islamic education curricula. The findings suggest that Islamic education, when adapted to modern challenges and integrated with innovative technologies, can play a pivotal role in preventing radicalization and fostering a more tolerant, inclusive society. The article concludes with recommendations for educators, policymakers, and stakeholders to adopt inclusive pedagogies, promote citizenship education, and leverage digital tools to enhance engagement and prevent extremist ideologies.